Risk Management in the Handling of Human Remains in Cargo at PT Dharma Bandar Mandala Soekarno Hatta - Mulyani Setyowati, Tri; Handayani, Sri; Amanda Widyasanti, Agti; Herma Oktavia, Sherlita; Wardana, Aditya; Ringan Purba, Okin (KnE Social Sciences, 2023)
This study aimed to analyze the risk management process for the special cargo of human remains. This qualitative study using a case study was conducted in a Freight Forwarding Companies in Indonesia. The data were obtained from observations, relevant documents and interviews. The result revealed the strategies used for risk management of transferring human remains in the company, including identifying the possible risks and preparing the actions. The company determined that the potential problems are the incompleteness of documents, unavailability of flight schedule, unresponsive cargo agent, coffin damage, and pick up of the coffin by the deceased’s family. To handle these risks, the company confirmed that the family or the related party had completed the documents, managed to send the human remains to the family or responsible parties soon, contacted the family to pick the human remains up immediately, apologized to the customers if there were any mishaps and gave sanctions to the irresponsible crews. Keywords: Risk Management, Special Cargo, Human Remains„ Special Cargo Services